Microbiota-Derived Metabolite Trimethylamine N-Oxide Protects Mitochondrial Energy Metabolism and Cardiac Functionality in a Rat Model of Right Ventricle Heart Failure - Videja, Melita; Vilskersts, Reinis; Korzh, Stanislava; Cirule, Helena; Sevostjanovs, Eduards; Dambrova, Maija; Makrecka-Kuka, Marina (Frontiers in Cell and Developmental Biology, 2021)
Aim: Trimethylamine N-oxide (TMAO) is a gut microbiota-derived metabolite synthesized in host organisms from specific food constituents, such as choline, carnitine and betaine. During the last decade, elevated TMAO levels have been proposed as biomarkers to estimate the risk of cardiometabolic diseases. However, there is still no consensus about the role of TMAO in the pathogenesis of cardiovascular disease since regular consumption of TMAO-rich seafood (i.e., a Mediterranean diet) is considered to be beneficial for the primary prevention of cardiovascular events. Therefore, the aim of this study was to investigate the effects of long-term TMAO administration on mitochondrial energy metabolism in an experimental model of right ventricle heart failure. Methods: TMAO was administered to rats at a dose of 120 mg/kg in their drinking water for 10 weeks. Then, a single subcutaneous injection of monocrotaline (MCT) (60 mg/kg) was administered to induce right ventricular dysfunction, and treatment with TMAO was continued (experimental groups: Control; TMAO; MCT; TMAO+MCT). After 4 weeks, right ventricle functionality was assessed by echocardiography, mitochondrial function and heart failure-related gene and protein expression was determined. Results: Compared to the control treatment, the administration of TMAO (120 mg/kg) for 14 weeks increased the TMAO concentration in cardiac tissues up to 14 times. MCT treatment led to impaired mitochondrial function and decreased right ventricular functional parameters. Although TMAO treatment itself decreased mitochondrial fatty acid oxidation-dependent respiration, no effect on cardiac functionality was observed. Long-term TMAO administration prevented MCT-impaired mitochondrial energy metabolism by preserving fatty acid oxidation and subsequently decreasing pyruvate metabolism. In the experimental model of right ventricle heart failure, the impact of TMAO on energy metabolism resulted in a tendency to restore right ventricular function, as indicated by echocardiographic parameters and normalized organ-to-body weight indexes. Similarly, the expression of a marker of heart failure severity, brain natriuretic peptide, was substantially increased in the MCT group but tended to be restored to control levels in the TMAO+MCT group. Conclusion: Elevated TMAO levels preserve mitochondrial energy metabolism and cardiac functionality in an experimental model of right ventricular heart failure, suggesting that under specific conditions TMAO promotes metabolic preconditioning-like effects.